2021
DOI: 10.1071/pc20068
|View full text |Cite
|
Sign up to set email alerts
|

The threat by the invasive African tulip tree,

Abstract: Expert knowledge is widely used for assessing the conservation status of little-known species. Pterocymbium oceanicum is a large, emergent tree endemic to Fiji. Experts classified the species as ‘Critically Endangered’ (IUCN Red List) in 2016 and estimated the population size at <250 mature individuals with the largest subpopulation consisting of a single stand of 100 individuals. We surveyed this stand and counted 133 individuals, which validated the expert estimate. However, we discovered an additional th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…(Sterculiaceae), Bischofia javanica Blume (Phyllanthaceae), and Dendrocnide harveyi (Seem.) Chew (Urticaceae) are the dominant tree species [38].…”
Section: Study Sitesmentioning
confidence: 99%
“…(Sterculiaceae), Bischofia javanica Blume (Phyllanthaceae), and Dendrocnide harveyi (Seem.) Chew (Urticaceae) are the dominant tree species [38].…”
Section: Study Sitesmentioning
confidence: 99%
“…The habitat of P. macranthum in SSR-XNNR is mainly tropical monsoon forest, a similar ecological niche to other species like P. tinctorum and P. oceanicum, and the Author-formatted, not peer-reviewed document posted on 11/04/2023. DOI: https://doi.org/10.3897/arphapreprints.e104785 tree is an iconic tree species to such forest type, even becoming dominant in some areas (Tripathi et al 2004;Keppel et al 2021;Hernandez et al 2021). Zhu et al (2015) confirmed that the tropical rainforests of Xishuangbanna are part of the southeast Asia tropical rainforests by analyzing floristics characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…(Rivers 2016) has drawn more attention. Keppel et al (2021) showed that P. oceanicum has a narrow ecological niche, that its habitats are degraded, and that its population may be threatened by an alien species of similar ecological niche (the invasion of Spathodea campanulata P.Beauv.). Only 433 individuals of P. resources, we confirmed that the species and the genus are new to China.…”
Section: Introductionmentioning
confidence: 99%
“…The eighth group was S. campanula, assigned its own functional group because it represents an introduced fast-growing pioneer taking advantage of degraded forest ecosystems [79] and competing with native vegetation. This niche has resulted in it either coexisting with or being a threat to native species [80][81][82][83][84][85]. Consequently, it represents a conspicuous species to monitor within various tropical insular landscapes, especially because its seedlings may have some shade tolerance [80].…”
Section: Temporal Trends In Functional Groupsmentioning
confidence: 99%